THE EFFECTS OF THE PERCEPTION OF ORGANIZATIONAL JUSTICE ON JOB SATISFACTION: A RESEARCH ON CNC OPERATOR EMPLOYEES IN ANKARA (Third Sector Social Economic Review, 2015)
The purpose of this study was to detect the effect of organizational justice perceptions (especially the subdimensions of the organizational justice which are distributional, procedural and interactional justice) on the job satisfaction. Research was carried out with 107 Cnc operator employees who work in Ankara Gölbaşı district. It was concluded that the three dimensions of organizational justice positively affects the job satisfaction. In particular, the procedural justice was found to have the most significant effect on the job satisfaction compared to the other two subdimensions.
Keywords: Organizational justice; Distributive justice; Procedural justice; Interactional Justice; Job satisfaction